Preemie Care: A Co-designed Digital Tool to Improve Communication Between Health Personnel and Parents of Preterm Infants - Mburu, Christine Wanjiru (Department of Computer Science, 2023)
Communication between parents and health providers is essential in the Neonatal Intensive Care Unit (NICU) settings to ensure both parties collaborate in infant care. However, in most NICUs, the interaction between parents and NICU staff is strained, thus hindering communication. These communication challenges are due to language, medical vocabulary and cultural barriers between NICU staff and mothers. These challenges create communication gaps, which disempower parents and frustrate health staff. To bridge NICU communication gaps, several researchers have deployed digital health interventions. However, although the existing NICU technologies have effectively improved NICU communication, most parents struggle to interact with these interventions because they do not fit parents' technical and literacy capabilities. These design gaps arise because parents were not fully included in the design process of the existing NICU digital interventions. In this research, we sought to address the communication gaps within the NICU environment by employing a co-design approach to develop a digital intervention that supports infant care journey in a low-resource NICU setting. The co-design process included six research phases that spanned over 32 months. We engaged mothers of premature infants and NICU staff throughout this process while focusing on identifying how best to involve NICU stakeholders in a codesign process to ensure that the final intervention was usable and useful. The co-design process led to the development of MoM connect workflow which was disqualified by mothers and NICU staff because it did not meet mothers' needs. We further engaged NICU stakeholders in the co-design process and agreed on developing Preemie Care (PMC) system, an educational resource tool that disseminated digital health videos in multiple languages and through multiple technologies to empower parents and NICU staff to work together and advocate for their preterm infants. PMC system was deployed at Groote Schuur NICU for eight months where we interacted with users and monitored it usage logs to evaluate its efficacy. Our empirical evidence revealed that access to health information improved parents and their social networks medical vocabulary, thus empowering them to engage with their peers and NICU staff. We also learned that sharing health information in multiple languages does not resolve the language barriers among multilingual NICU parents. Instead, our results show that bilingual parents prefer accessing health information in multiple languages to improve their medical vocabulary and understandability, thus empowering them to engage in their infants' health care and decision-making. Hence, this research provides the design mechanisms for a NICU intervention to bridge communication gaps between bilingual parents and NICU staff. This work contributes to the field of Human-Computer Interaction(HCI) by highlighting the ethical and methodological considerations to engage NICU stakeholders interacting in a sensitive NICU setting in a collaborative co-design process. We also contribute to HCI knowledge by providing design mechanisms for a NICU intervention meant to bridge communication gaps between bilingual parents and NICU staff in a low-resource setting and design features of a digital NICU intervention that enhance family-centred care in the NICU setting.